Answer:
![\kappa = \frac{1}{2 b}](https://tex.z-dn.net/?f=%5Ckappa%20%3D%20%5Cfrac%7B1%7D%7B2%20b%7D)
Explanation:
The equation for kappa ( κ) is
![\kappa = \frac{a}{a^2 + b^2}](https://tex.z-dn.net/?f=%5Ckappa%20%3D%20%5Cfrac%7Ba%7D%7Ba%5E2%20%2B%20b%5E2%7D)
we can find the maximum of kappa for a given value of b using derivation.
As b is fixed, we can use kappa as a function of a
![\kappa (a) = \frac{a}{a^2 + b^2}](https://tex.z-dn.net/?f=%5Ckappa%20%28a%29%20%3D%20%5Cfrac%7Ba%7D%7Ba%5E2%20%2B%20b%5E2%7D)
Now, the conditions to find a maximum at
are:
![\frac{d \kappa(a)}{da} \left | _{a=a_0} = 0](https://tex.z-dn.net/?f=%5Cfrac%7Bd%20%5Ckappa%28a%29%7D%7Bda%7D%20%5Cleft%20%7C%20_%7Ba%3Da_0%7D%20%3D%200)
![\frac{d^2\kappa(a)}{da^2} \left | _{a=a_0} < 0](https://tex.z-dn.net/?f=%5Cfrac%7Bd%5E2%5Ckappa%28a%29%7D%7Bda%5E2%7D%20%20%5Cleft%20%7C%20_%7Ba%3Da_0%7D%20%3C%200)
Taking the first derivative:
![\frac{d}{da} \kappa = \frac{d}{da} (\frac{a}{a^2 + b^2})](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bda%7D%20%5Ckappa%20%3D%20%5Cfrac%7Bd%7D%7Bda%7D%20%20%28%5Cfrac%7Ba%7D%7Ba%5E2%20%2B%20b%5E2%7D%29)
![\frac{d}{da} \kappa = \frac{1}{a^2 + b^2} \frac{d}{da}(a)+ a * \frac{d}{da} (\frac{1}{a^2 + b^2} )](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bda%7D%20%5Ckappa%20%3D%20%5Cfrac%7B1%7D%7Ba%5E2%20%2B%20b%5E2%7D%20%5Cfrac%7Bd%7D%7Bda%7D%28a%29%2B%20a%20%2A%20%5Cfrac%7Bd%7D%7Bda%7D%20%20%28%5Cfrac%7B1%7D%7Ba%5E2%20%2B%20b%5E2%7D%20%29)
![\frac{d}{da} \kappa = \frac{1}{a^2 + b^2} * 1 + a * (-1) (\frac{1}{(a^2 + b^2)^2} ) \frac{d}{da} (a^2+b^2)](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bda%7D%20%5Ckappa%20%3D%20%5Cfrac%7B1%7D%7Ba%5E2%20%2B%20b%5E2%7D%20%2A%201%20%2B%20a%20%2A%20%28-1%29%20%20%28%5Cfrac%7B1%7D%7B%28a%5E2%20%2B%20b%5E2%29%5E2%7D%20%29%20%5Cfrac%7Bd%7D%7Bda%7D%20%20%28a%5E2%2Bb%5E2%29)
![\frac{d}{da} \kappa = \frac{1}{a^2 + b^2} * 1 - a (\frac{1}{(a^2 + b^2)^2} ) (2* a)](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bda%7D%20%5Ckappa%20%3D%20%5Cfrac%7B1%7D%7Ba%5E2%20%2B%20b%5E2%7D%20%2A%201%20-%20a%20%20%28%5Cfrac%7B1%7D%7B%28a%5E2%20%2B%20b%5E2%29%5E2%7D%20%29%20%282%2A%20a%29%20)
![\frac{d}{da} \kappa = \frac{1}{a^2 + b^2} * 1 - 2 a^2 (\frac{1}{(a^2 + b^2)^2} )](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bda%7D%20%5Ckappa%20%3D%20%5Cfrac%7B1%7D%7Ba%5E2%20%2B%20b%5E2%7D%20%2A%201%20-%20%202%20a%5E2%20%20%28%5Cfrac%7B1%7D%7B%28a%5E2%20%2B%20b%5E2%29%5E2%7D%20%29%20%20)
![\frac{d}{da} \kappa = \frac{a^2+b^2}{(a^2 + b^2)^2} - 2 a^2 (\frac{1}{(a^2 + b^2)^2} )](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bda%7D%20%5Ckappa%20%3D%20%5Cfrac%7Ba%5E2%2Bb%5E2%7D%7B%28a%5E2%20%2B%20b%5E2%29%5E2%7D%20%20-%20%202%20a%5E2%20%20%28%5Cfrac%7B1%7D%7B%28a%5E2%20%2B%20b%5E2%29%5E2%7D%20%29%20%20)
![\frac{d}{da} \kappa = \frac{1}{(a^2 + b^2)^2} (a^2+b^2 - 2 a^2)](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bda%7D%20%5Ckappa%20%3D%20%5Cfrac%7B1%7D%7B%28a%5E2%20%2B%20b%5E2%29%5E2%7D%20%28a%5E2%2Bb%5E2%20-%20%202%20a%5E2%29%20)
![\frac{d}{da} \kappa = \frac{b^2 - a^2}{(a^2 + b^2)^2}](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bda%7D%20%5Ckappa%20%3D%20%5Cfrac%7Bb%5E2%20-%20%20a%5E2%7D%7B%28a%5E2%20%2B%20b%5E2%29%5E2%7D%20)
This clearly will be zero when
![a^2 = b^2](https://tex.z-dn.net/?f=a%5E2%20%3D%20b%5E2)
as both are greater (or equal) than zero, this implies
![a=b](https://tex.z-dn.net/?f=a%3Db)
The second derivative is
![\frac{d^2}{da^2} \kappa = \frac{d}{da} (\frac{b^2 - a^2}{(a^2 + b^2)^2} )](https://tex.z-dn.net/?f=%5Cfrac%7Bd%5E2%7D%7Bda%5E2%7D%20%5Ckappa%20%3D%20%5Cfrac%7Bd%7D%7Bda%7D%20%28%5Cfrac%7Bb%5E2%20-%20%20a%5E2%7D%7B%28a%5E2%20%2B%20b%5E2%29%5E2%7D%20%29)
![\frac{d^2}{da^2} \kappa = \frac{1}{(a^2 + b^2)^2} \frac{d}{da} ( b^2 - a^2 ) + (b^2 - a^2) \frac{d}{da} ( \frac{1}{(a^2 + b^2)^2} )](https://tex.z-dn.net/?f=%5Cfrac%7Bd%5E2%7D%7Bda%5E2%7D%20%5Ckappa%20%3D%20%5Cfrac%7B1%7D%7B%28a%5E2%20%2B%20b%5E2%29%5E2%7D%20%5Cfrac%7Bd%7D%7Bda%7D%20%28%20b%5E2%20-%20%20a%5E2%20%29%20%2B%20%28b%5E2%20-%20%20a%5E2%29%20%5Cfrac%7Bd%7D%7Bda%7D%20%28%20%5Cfrac%7B1%7D%7B%28a%5E2%20%2B%20b%5E2%29%5E2%7D%20%20%29%20%20)
![\frac{d^2}{da^2} \kappa = \frac{1}{(a^2 + b^2)^2} ( -2 a ) + (b^2 - a^2) (-2) ( \frac{1}{(a^2 + b^2)^3} ) (2a)](https://tex.z-dn.net/?f=%5Cfrac%7Bd%5E2%7D%7Bda%5E2%7D%20%5Ckappa%20%3D%20%5Cfrac%7B1%7D%7B%28a%5E2%20%2B%20b%5E2%29%5E2%7D%20%28%20-2%20%20a%20%29%20%2B%20%28b%5E2%20-%20%20a%5E2%29%20%28-2%29%20%28%20%5Cfrac%7B1%7D%7B%28a%5E2%20%2B%20b%5E2%29%5E3%7D%20%20%29%20%282a%29%20)
![\frac{d^2}{da^2} \kappa = \frac{-2 a}{(a^2 + b^2)^2} + (b^2 - a^2) (-2) ( \frac{1}{(a^2 + b^2)^3} ) (2a)](https://tex.z-dn.net/?f=%5Cfrac%7Bd%5E2%7D%7Bda%5E2%7D%20%5Ckappa%20%3D%20%5Cfrac%7B-2%20%20a%7D%7B%28a%5E2%20%2B%20b%5E2%29%5E2%7D%20%2B%20%28b%5E2%20-%20%20a%5E2%29%20%28-2%29%20%28%20%5Cfrac%7B1%7D%7B%28a%5E2%20%2B%20b%5E2%29%5E3%7D%20%20%29%20%282a%29%20)
We dcan skip solving the equation noting that, if a=b, then
![b^2 - a^2 = 0](https://tex.z-dn.net/?f=b%5E2%20-%20%20a%5E2%20%3D%200)
at this point, this give us only the first term
![\frac{d^2}{da^2} \kappa = \frac{- 2 a}{(a^2 + a^2)^2}](https://tex.z-dn.net/?f=%5Cfrac%7Bd%5E2%7D%7Bda%5E2%7D%20%5Ckappa%20%3D%20%5Cfrac%7B-%202%20%20a%7D%7B%28a%5E2%20%2B%20a%5E2%29%5E2%7D%20)
if a is greater than zero, this means that the second derivative is negative, and the point is a minimum
the value of kappa is
![\kappa = \frac{b}{b^2 + b^2}](https://tex.z-dn.net/?f=%5Ckappa%20%3D%20%5Cfrac%7Bb%7D%7Bb%5E2%20%2B%20b%5E2%7D)
![\kappa = \frac{b}{2* b^2}](https://tex.z-dn.net/?f=%5Ckappa%20%3D%20%5Cfrac%7Bb%7D%7B2%2A%20b%5E2%7D)
![\kappa = \frac{1}{2 b}](https://tex.z-dn.net/?f=%5Ckappa%20%3D%20%5Cfrac%7B1%7D%7B2%20b%7D)